Perlindungan Hukum Terhadap Konsumen Yang Dirugikan Dalam Transaksi Jual Beli Barang di Online Shop - Aldi Rozzaq Bimantara; Edi Pranoto (Amal Insani Foundation, 2023)
The use of electronic media to function as digital data in making agreements will have an impact on the performance of companies that carry out their activities using electronic media such as the internet, but agreements made via the internet do not mean they do not cause problems. This problem is with the development of crime that utilizes the internet network, namely the rise of fraud via the internet, especially in online transactions. The government's efforts to provide consumer protection have been reflected in the establishment of Law No. 6 of 19999 concerning Consumer Protection. Where it has been regulated regarding the rights and obligations of consumers. In addition, there are rights and obligations for the seller. Therefore the authors are interested in conducting research with the title